UJI KETERKAITAN FENOMENA KEDATANGAN KOMET 1P/HALLEY TAHUN 760 MASEHI DENGAN ISI PRASASTI DINOYO MELALUI PENDEKATAN ARKEOASTRONOMI - Ide Nada Imandiharja; Mochamad Ikbal Arifyanto (AMERTA, 2023)
Abstract. Testing The Connection between The Appearance of Comet 1P/Halley in 760 CE and The Contents of Dinoyo Inscription through The Archaeoastronomical Approach. Astronomical knowledge has been attached to the ancestors of the Indonesian people since ancient times. The assumption raised in this study is that the Dinoyo Inscription is a response from the Kanjuruhan community to the phenomenon of the arrival of comet 1P/Halley which was identified in the same year as the year the inscription was issued. This research was conducted from the point of view of archeoastronomy. In this study, three types of tests were carried out, namely tests in chronological, geographical, and cultural aspects. Tests on chronological and geographical aspects use inscription data reviewed with the Stellarium astronomy application. Meanwhile, testing on cultural aspects is carried out by interpreting the symbols contained in the contents of the inscriptions. The results of these tests are used to strengthen the argument about the existence of a relationship between the contents of the Dinoyo Inscription and the arrival of comet 1P/Halley. The lack of data hampers the validity of the arguments that have been developed. However, based on the results of the tests that have been carried out, the behavior of the Kanjuruhan people on the Dinoyo Inscription is a response to the phenomenon of the return of comet 1P/Halley in 760 CE. Keywords: Dinoyo Inscription, Comet 1P/Halley, Archaeoastronomy   Abstrak. Pengetahuan astronomi telah melekat pada nenek moyang bangsa Indonesia sejak zaman dahulu kala. Dugaan yang dimunculkan dalam penelitian ini adalah bahwa Prasasti Dinoyo merupakan respon masyarakat Kanjuruhan terhadap fenomena kedatangan komet 1P/Halley yang teridentifikasi pada tahun yang sama dengan tahun dikeluarkannya prasasti. Penelitian ini dilakukan dalam pendekatan arkeoastronomi. Dalam penelitian ini, tiga jenis pengujian dilakukan, yaitu pengujian dalam aspek kronologis, geografis, dan budaya. Pengujian pada aspek kronologis dan geografis menggunakan data prasasti yang ditinjau dengan aplikasi astronomi Stellarium. Sementara itu, pengujian pada aspek budaya dilakukan dengan menafsirkan simbol-simbol yang terdapat pada isi prasasti. Hasil dari pengujian tersebut digunakan untuk memperkuat argumen tentang adanya hubungan antara isi Prasasti Dinoyo dengan peristiwa kedatangan komet 1P/Halley. Kurangnya data menghambat validitas argumen yang telah disusun. Namun demikian, berdasarkan hasil pengujian yang telah dilakukan, perilaku Masyarakat Kanjuruhan pada Prasasti Dinoyo merupakan respon atas fenomena kedatangan kembali komet 1P/Halley pada tahun 760 Masehi. Kata kunci: Prasasti Dinoyo, Komet 1P/Halley, Arkeoastronomi.